Analysis of the Effect of Increasing Load on Voltage Profile in Electric Power Distribution System - Anggara, Doni; Danial, Danial; Abidin, Zainal (Ridwan Institute, 2025)
Power distribution systems are critical in delivering electricity reliably, but they are highly susceptible to voltage quality degradation due to uneven load growth. The research problem addressed in this study is how increasing loads affect the voltage profile and power losses in a distribution system, particularly in scenarios of rapid demand growth. The objective of this study is to analyze the impact of load increases on voltage levels and system efficiency in the IEEE 33-bus distribution network. The study employs a quantitative simulation method using the Newton-Raphson power flow technique in PSAT, integrated with MATLAB. Load scenarios were simulated at 25%, 50%, 75%, 100%, 125%, and 150% of the base load. Results indicate that as load increases, voltage levels at several buses, especially those farthest from the source, decrease significantly. The minimum system voltage drops from 11.55 kV under initial conditions to 9.39 kV at a 150% load increase, resulting in a voltage drop of up to 25.8%. Furthermore, both active and reactive power losses increase with higher load levels, indicating reduced system efficiency. The study implies that distribution networks like the IEEE 33-bus system require mitigation strategies, such as voltage regulation and loss reduction measures, to maintain voltage quality and energy efficiency under high load conditions.